Morbidity and mortality according to age following gastrectomy for gastric cancer. Issue 9 (23rd April 2018) - Nelen, S. D.; Bosscha, K.; Lemmens, V. E. P. P.; Hartgrink, H. H.; Verhoeven, R. H. A.; de Wilt, J. H. W.; ,
Abstract : Background: This study investigated age‐related differences in surgically treated patients with gastric cancer, and aimed to identify factors associated with outcome. Methods: Data from the Dutch Upper Gastrointestinal Cancer Audit were used. All patients with non‐cardia gastric cancer registered between 2011 and 2015 who underwent surgery were selected. Patients were analysed by age group (less than 70 years versus 70 years or more). Multivariable logistic regression was used to assess the influence of clinicopathological factors on morbidity and mortality. Results: A total of 1109 patients younger than 70 years and 1206 aged 70 years or more were included. Patients aged at least 70 years had more perioperative or postoperative complications (41·2 versus 32·5 per cent; P < 0·001) and a higher 30‐day mortality rate (7·9 versus 3·2 per cent; P < 0·001) than those younger than 70 years. In multivariable analysis, age 70 years or more was associated with a higher risk of complications (odds ratio 1·29, 95 per cent c.i. 1·05 to 1·59). Postoperative mortality was not significantly associated with age. In the entire cohort, morbidity and mortality were influenced most by ASA grade, neoadjuvant chemotherapy and type of resection. Conclusion: ASA grade, neoadjuvant chemotherapy and type of resection are independent predictors of morbidity and death in patients with gastric cancer, irrespective of age. Abstract : Age does not matter